The Effect of COVID-19 Pandemic Information and Trusts towards Online Retailers on Online Consumers’ Risk Perception and Purchasing Behaviour - Astuti, Rifelly Dewi; Balqiah, Tengku Ezni; Kusumastuti, Ratih Dyah; Viverita, V. (APMBA (Asia Pacific Management and Business Application), 2026)
Understanding how information influences consumer behavior during a public health crisis is crucial for both businesses and policymakers in managing risk communication and sustaining economic activity. Since the announcement of the first case of COVID-19 in early March 2020, the timeline across both mass and social media has been dominated by information about the virus. This information has increased public awareness of the risk of contracting COVID-19 when engaging in activities outside the home, including shopping. As a result, most shopping activities have shifted online. However, online shopping does not entirely eliminate the risk of virus transmission. This study aims to investigate the impact of COVID-19 information in mass and social media on trust in online retailers and online shopping behavior, with risk perception as a mediating variable. A survey was conducted with 1,212 respondents across Indonesia, and the data were analyzed using structural equation modeling. The results indicate that COVID-19-related information directly influences consumers’ online purchasing behavior, while trust in online retailers affects behavior indirectly through the mediation of risk perception.